Role of population screening in identification of chronic kidney disease. - M. Yu. Dudko; O. N. Kotenko; A. V. Malkoch (Лечащий Врач)
The issues of identification of chronic kidney disease (CKD) at the early stages were studied, necessity of timely and proper nephroprotective therapy was stressed, as well as treatment of the main disease, revealing and control of the complications. Complex management of CKD patients prolongs the time before dialysis and significantly increases life quality of such patients.